Znalezisko denarów Bolesława Kędzierzawego na stanowisku 1 w Wilkowicach, gm. Wartkowice - Blaszczyk, Jacek (Acta Universitatis Lodziensis. Folia Archaeologica, 1996)
Most early medieval coins come from hoards, and only few are revealed by archaeological excavations. The Wilkowice coins were found in a feature defined as a hut, which contained numerous sherds of pottery made by hand and finished on the wheel. The hut was located within an open settlement. Denarii of this type (no 54 according to Stronczyński’s classification) were struck in the times of Bolesław the Curly after 1160. Accordingly, the feature that contained them dates from the turn of the 3rd/4th or from the 4th quarter of the 12th century.